Mineralogy and Genesis of Soils in Uuiversiti Pertanian Malaysia, Serdang, Selangor - Jusop, Shamsuddin; Darus, A. (1979)
Soils of Universiti Pertanian Malaysia were surveyed and studied in order to determine their mineralogy and genesis. The results of the study showed that there were four major soil series on the Universiti Pertanian farm. Two of these series, namely Melaka and IVlunchong Series, were taxonomically classified as Tropeptic Haplorthox, while the other two, namely Serdang and Bungor Series, were classified as Typic Paleudult. The structure of the soils was found to be weak. The texture was clay in the case of Melaka, Munchong and Bungor Series and sandy clay loam in the case of Serdang Series. Melaka Series soil which contained petroplinthite occur as capping on top of hills. Soils of Munchong, Bungor and Serdang occur either on the slope or on the lower position than Melaka Series. All soils were extremely weathered. The dominant clay minerals were kaolinite, gibbsite and goethite; 2:1 type of clay mineral was virtually absent, except possibly some illite in Melaka Series. The pH was low, and so were exchangeable cations, CEC and %base saturation. On the other hand, exchangeable Al and H were significantly high